Internal control mechanisms to improve the results of a social programa: Programa Jóvenes a la Obra - Almanza Hurtado, Diana (2019)
Objective: To identify the internal control mechanisms that contribute to the improvement of the results of the National Youth Employment Program Young People, through a budgetary execution, signing of agreements and the monitoring of the programmed tasks. Method: The non – experimental design was used, qualitative in which pretend to respond to a little studied phenomenon. Being a research type exploratory – descriptive, it was elaborated surveys to collect relevant information to the subject in which it was use the Likert scale. The data collection was obtained from a population of 80 people of the youth to the work program, who worked during the 2014 period and for the sample the method of non-probabilistic sampling was used. Results: The implementation of internal control mechanisms will improve the results of the Youth to Work Program while optimizing its management. Conclusions: The mechanisms of internal control within the framework of budgetary execution, execution of agreements and follow-up of scheduled tasks will contribute to the improvement of the management of the Youth to Work Program, attaining an increase in the labor insertion of the beneficiaries.